Fluid flow and heat transfer investigation of blood with nanoparticles through porous vessels in the presence of magnetic field. (August 2018) - Usman, Muhammad; Mohyud Din, Syed Tauseef; Zubair, Tamour; Hamid, Muhammad; Wang, Wei
In this study, the blood flow was investigated involving nanoparticles through porous blood vessels in the presence of magnetic field by means of collocation and least squares techniques. Blood was assumed to be non-Newtonian fluid having nanoparticles in which different models were used to determine the viscosity of the nanofluids. Vogel's, Reynolds, variable, and constant viscosity models were discussed by using the two aforementioned techniques. Hence, we compared our results with a numerical technique RK-4 and already existing results to show the credibility of our solutions. Further, some physical parameters and their effects are also stated in this research. Increase in the thermophoresis parameter and pressure gradient along with the decrease in the Brownian motion parameter provide a rapid change in the velocity profile, which has been disclosed by results. Additionally, a dramatic change in the velocity has been realized by using Vogel's model.